2006
DOI: 10.1111/j.1365-2966.2005.09982.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of near-infrared, optical and X-ray luminosity for early-type galaxies

Abstract: The relation between X‐ray luminosity and near‐infrared (NIR) luminosity for early‐type galaxies has been examined. NIR luminosities should provide a superior measure of stellar mass compared to optical luminosities used in previous studies, especially if there is significant star formation or dust present in the galaxies. However, we show that the X‐ray–NIR relations are remarkably consistent with the X‐ray–optical relations. This indicates that the large scatter of the relations is dominated by scatter in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
92
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 80 publications
(162 reference statements)
10
92
0
Order By: Relevance
“…Hot, warm and cold gas detections have been reported by several authors (eg. Caon et al 2000;Mathews & Brighenti 2003;Sarzi et al 2006Sarzi et al , 2013Mulchaey & Jeltema 2010;Ellis & O'Sullivan 2006;Davis et al 2011;Serra et al 2012) The cold ISM is often spatially extended, with irregular distribution and kinematics (Caon et al 2000). Dust is also present in all the phases of the ISM (Temi et al 2005(Temi et al , 2009Smith et al 2012), and the dust-to-gas ratio can be used to track down the origin of the cold gas.…”
mentioning
confidence: 99%
“…Hot, warm and cold gas detections have been reported by several authors (eg. Caon et al 2000;Mathews & Brighenti 2003;Sarzi et al 2006Sarzi et al , 2013Mulchaey & Jeltema 2010;Ellis & O'Sullivan 2006;Davis et al 2011;Serra et al 2012) The cold ISM is often spatially extended, with irregular distribution and kinematics (Caon et al 2000). Dust is also present in all the phases of the ISM (Temi et al 2005(Temi et al , 2009Smith et al 2012), and the dust-to-gas ratio can be used to track down the origin of the cold gas.…”
mentioning
confidence: 99%
“…However, Ellis & O'Sullivan (2006) showed that replacing LB by K-band luminosity in Fig.1, results in a very similar scatter.…”
Section: Sources Of Scatter In L X -L Optmentioning
confidence: 95%
“…Galaxy environment - Ellis & O'Sullivan (2006) found no clear environmental trend in LX /LB , apart from the high values apparent in BGGs and BCGs. However, recent studies with Chandra, which is better able to resolve galaxy emission, show that LX /LB is suppressed by a factor ∼3-4 in non-central galaxies within both clusters (Sun et al (2007)) and groups (Jeltema et al (2008)).…”
Section: Sources Of Scatter In L X -L Optmentioning
confidence: 99%
See 2 more Smart Citations